The Implementation of ‘Merdeka Belajar’ Curriculum in the English Teaching Process - Seftiwin Sunga; Moon Hidayati Otuluwa; Helena Badu (Transbahasa, 2024)
The purpose of this study is to describe the implementation process of the Merdeka Belajar curriculum in English teaching in the classroom. This research employs a qualitative descriptive method to analyze the data. The study was conducted at SMA N 1 Tilamuta, focusing on English subject teachers and 10th-grade students. The results indicate that only 4 out of 12 teaching activities were effectively implemented during the teaching process. The first activity involves teachers organizing learning based on students' needs while connecting it to real-world contexts, the environment, and cultures that interest students, achieving 94.4%. Next, teachers designed interactive learning to facilitate structured, integrated, and productive interactions between teachers and students, among students, and between students and learning materials, reaching 88.89%. Teachers also applied various teaching methods with a student-centered approach, achieving 72.22%. Finally, teachers assigned tasks to assess students' understanding of the material taught, with a result of 55.55%. The study concludes that the implementation of the Merdeka curriculum in English learning at SMA N 1 Tilamuta still has significant shortcomings in pre-activities, main activities, and post-activities.